AI-Driven Edge Computing in the Cloud Era: Challenges and Opportunities - Manduva, Vinay Chowdary (International Journal of Scientific Research and Management (IJSRM), 2023)
Towards understanding the synergy of integrating AI with edge computing within the emerging cloud computing environment, this paper seeks to examine the pertinent literature study. Edge computing AI maybe defined as implementing Artificial intelligence at the edges or remote local servers within the network usually near the data source. This paper aims at establishing the Implications of this integration on the matters such as scalability, latency, data privacy, security, among other aspects of resource constraint. They also explain possible advantages which include; real time analytical processing, low bandwidth consumption and independent operation of edge devices. This paper aims to offer a broad snapshot of current AI-drivenedge computing advances and future research directions by summarizing prior literature and conducting acurrent technology assessment.